Hutchinson–Gilford progeria syndrome through the lens of transcription - Miron Prokocimer; Rachel Barkan; Yosef Gruenbaum (2013)
Lamins are nuclear intermediate filaments. In addition to their structural roles, they are implicated in basic nuclear functions such as chromatin organization, DNA replication, transcription, DNA repair, and cell-cycle progression. Mutations in human LMNA gene cause several diseases termed laminopathies. One of the laminopathic diseases is Hutchinson-Gilford progeria syndrome (HGPS), which is caused by a spontaneous mutation and characterized by premature aging. HGPS phenotypes share certain similarities with several apparently comparable medical conditions, such as aging and atherosclerosis, with the conspicuous absence of neuronal degeneration and cancer rarity during the short lifespan of the patients. Cell lines from HGPS patients are characterized by multiple nuclear defects, which include abnormal morphology, altered histone modification patterns, and increased DNA damage. These cell lines provide insight into the molecular pathways including senescence that require lamins A and B1. Here, we review recent data on HGPS phenotypes through the lens of transcriptional deregulation caused by lack of functional lamin A, progerin accumulation, and lamin B1 silencing.